Equilibrium Yield Curve, the Phillips Curve, and Monetary Policy - Katagiri, Mitsuru (IMF Working Papers; Working Paper ;, 2018)
Upward sloping yield curves are hard to reconcile with the positive association between income and inflation (the Phillips curve) in consumption-based asset pricing models. Using US and UK data, this paper shows inflation is negatively correlated with long-run income growth but positively correlated with cyclical income, thus enabling the model to replicate positive and sizable term premiums, along with the Phillips curve over business cycles. Quantitative analyses also emphasize the importance of monetary policy, predicting that a permanently low growth and low inflation environment would precipitate flatter yield curves due to constraints to monetary policy around the zero lower bound.